Settlement of International Disputes Through Diplomacy: The Case of the Collision of an Indonesian Navy Ship by a Vietnamese Fishing Vessel - Gede Jeje Vijanathananda Sara; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Dinasti Research, 2026)
This study aims to determine and examine the international dispute resolution actions taken by Indonesia in the case of the collision of an Indonesian Navy ship by a Vietnamese fisheries surveillance vessel in violation of the COLREG 1972 and UNCLOS 1982 regulations. The type of research used is normative legal research, with a legislative approach, a case approach, and a conceptual approach. The sources of legal materials used are inseparable from the existing rules in national law and international law, with a special focus on regulations governing ship collisions and maritime law. The legal material collection technique used is by exploring the normative framework and also document study techniques using legal materials that discuss the theories of maritime law, especially COLREG 1972 and UNCLOS 1982. The results of the study indicate that the resolution of international legal problems carried out by the State of Vietnam against the State of Indonesia regarding violations of COLREG 1972 and UNCLOS 1982 in the Indonesian ZEE was resolved through maritime diplomacy efforts.